The Struggle of Generation Z Mothers Against Myths in Complementary Feeding Practices for Children Aged 6–24 Months in Ngabab Village, Pujon District - Faiza, Dhea Almira Putri; Anggraini, Ika Rizki; Ilmiasih, Reni; Aini, Nurul; Nurbatra, Laela Hikmah (Jurnal Perempuan dan Anak, 2026)
The provision of appropriate Complementary Feeding (CF) for toddlers aged 6-24 months is important to support optimal growth, prevent stunting, and meet nutritional needs during the golden period. However, challenges such as lack of family support and psychological pressure, including pressure from in-laws who prohibit the provision of animal protein because they worry the toddler will smell fishy, so the mother is only allowed to give clear vegetable soup and tempeh, making it an obstacle in the process of providing CF. This study aims to understand the struggles of gen Z mothers' against traditional myths in providing CF to toddlers aged 6-24 months, including challenges, family support, and efforts to overcome obstacles, to improve CF practices and prevent stunting. Using a qualitative research design with a case study strategy. Data collection employed semi-structured interviews with main participants Mrs. R (mother) and Mr. R (father). Participant selection used purposive sampling based on inclusion-exclusion criteria. Data were collected, recorded, transcribed, and analyzed thematically. Data validity was validated through source triangulation. This study identified 7 themes: 1). Consistency in providing CF; 2). Challenges in providing CF; 3). Emotional feelings; 4). High maternal knowledge about CF; 5). Family support; 6). Efforts made to overcome faced challenges; 7). Success in physical growth and toddler development changes. Despite psychological barriers, support from the nuclear family, especially the husband, enables successful positive growth changes such as increased toddler weight. This study emphasizes the importance of family support, stress management, and health education to improve CF practices for preventing stunting